Uma arquitetura para monitoramento de banco de dados e recomendações utilizando sistema de banco de dados ativos - Santos, Paulo Henrique dos (2014)
Integrated environments monitoring can become complex with heterogeneous databases, due to the particularities in the language syntax and available tools. In particular, active databases allow developing mechanisms and automation of processes involving data or objects. This work proposes the development of an architecture to identify and monitor DDL (Data Definition Language), exploring the active databases and recommendations approach. This architecture could be explored in several ways: simple monitoring of DDL events in one or more databases, or recommendation of future DDLs or settings within the monitored database. In this context, this work proposes: (i) an integrated architecture of active databases and recommendation; (ii) the adaptation of a recommendation algorithm; and (iii) the validation of concepts through a prototype.